A company’s business strategies for participating in ecosystems - Andreeva E.L. (Ural State University of Economics, 2018)
In the context of today’s economic situation, where, on the one hand, the policy of “breakthrough development” is proclaimed and implemented and, on the other hand, it is necessary to overcome new global challenges, there is a need for substantiating the changes in corporate business strategies. The changes increase the relevance of finding effective business adaptation mechanisms and evaluating the expediency of their scientific development. The methodological basis of the study includes the concept of the ecosystem, entrepreneurship theory, provisions of startup methodology (Lean Canvas, Customer Development, Lean Startup). The authors apply the methods of system, structural-functional and comparative analysis. The article generalizes theoreticalmethodological foundations of entrepreneurship ecosystems including the biological, structural and innovation approaches; reveals the methodological peculiarities of entrepreneurship ecosystems’ formation; discusses the major trends in entrepreneurship ecosystems that are beyond the scope of mere response and adaptation of business. We distinguish between four types of managerial business strategies – Cheburashka, Cloning, Sly fox and Hunting for elephant – and look at their distinguishing characteristics. The distinctive feature of management, which is based on participation of entrepreneurial structures in ecosystems, lies in coordinating environmental changes with companies’ activity through introduction of relevant business strategies. The authors prove that companies demonstrate a high positive potential for participating in entrepreneurship ecosystems but it is not uncommon that they do not use it as a means of corporate governance in the conditions of environmental challenges.